Food system emissions: a review of trends, drivers, and policy approaches, 1990–2018 - Cerutti, Nicola; Lamb, William F; Crippa, Monica; Leip, Adrian; Solazzo, Efisio; Tubiello, Francesco N; Minx, Jan C (Environmental research letters, 2023)
The food system, spanning from pre-production processes to post-production stages, is responsible for about one third of global greenhouse gas emissions and requires significant mitigation efforts to prevent dangerous levels of global warming. This article summarises trends and drivers of global food system emissions from 1990 to 2018. We highlight regional diversity in patterns of food system emissions and identify the highest global emitters. While food system emissions have stabilised in some regions and countries, global emissions are increasing, with growth in certain sectors and countries outweighing the handful of cases where sustained emissions reductions have been realised. Emissions from livestock rearing account for a large portion of global emissions, and the contribution of post-production emissions is steadily increasing in all regions. We also provide an overview of food system policies at the national level, mapping them to each emissions segment. This highlights the significant shortfall in policy activity required to address the challenge of climate change mitigation in general, and the impacts of livestock and post-production emissions in particular. Our work lays the groundwork for addressing specific country-level questions on optimal policy pathways to achieve emission reductions.